2011
DOI: 10.1080/02571862.2011.10640007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and varietal effects on tiller population development of sugarcane (Saccharum OfficinarumL.)

Abstract: Tillers carry leaves, determine leaf area index and indirectly influence the amount of photosynthetically active radiation (PAR) intercepted by the sugarcane canopy. Tillers develop into stalks, the sink for the products of photosynthesis. The objective of this study was to investigate the effects of seasons and varieties on tiller population development trends and parameters using different varieties (ZN6, ZN7, N14 and NCo376). Three replicated experiments were established in early (March), mid (July) and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Shoot populations increased up to 4 MAP/4 MAH, then decreased from 4-6 MAP/4-5 MAH to a stable 6-8 MAP/5-6 MAH level. These shoot population changes were consistent with Zhou & Shoko's (2011) observation in Zimbabwe. Shoot populations contribute to sugarcane yield.…”
Section: Growth Of Pc and Rc-1 Sugarcanesupporting
confidence: 91%
“…Shoot populations increased up to 4 MAP/4 MAH, then decreased from 4-6 MAP/4-5 MAH to a stable 6-8 MAP/5-6 MAH level. These shoot population changes were consistent with Zhou & Shoko's (2011) observation in Zimbabwe. Shoot populations contribute to sugarcane yield.…”
Section: Growth Of Pc and Rc-1 Sugarcanesupporting
confidence: 91%
“…Tillering of early‐season crops occurs in the winter months of May to August, whereas that for the late season occurs in summer months of December to February. Previous studies (Zhou and Shoko, 2011) showed lower peak tiller and final stalk population in late‐season than in early‐season crops, suggesting that fewer stalks in late‐season crops develop to millable stalks than in early‐season crops. Stalk elongation for early‐season crops occurs during the summer months from August to March, when plant growth conditions such as rainfall, temperature, and solar radiation are highest, providing conditions for maximum photosynthesis for biomass accumulation.…”
Section: Discussionmentioning
confidence: 86%
“…Early-season harvesting starts during the late summer rains in March when the crop is still actively growing. Late-season crops grow through winter during peak stalk elongation (Zhou and Shoko, 2011), resulting in low cane yield because low temperatures suppress stalk elongation in favor of sucrose accumulation. High cane yield and low sucrose content are characteristic of early season, whereas the opposite is true for late season.…”
Section: Location and Seasonal Effects On Irrigated Sugarcane Breedinmentioning
confidence: 99%
“…Therefore, the DS had a more complex structure for LAI simulations, which was affected by the number of stalks and phytomers, which represent a better approximation of the sugarcane development (Lou et al, 2013;Zhou and Shoko, 2011). This mechanism might explain part of the better accuracy and precision of DS for calibration and evaluation steps (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…The target variable to be improved was the SFY, but the variable assimilated was LAI, and between LAI and SFY there are several complex relationships affected by many other factors . Also, the LAI of sugarcane has a considerable variation among genotype and environment (Lou et al, 2013;, which reflects in the relationship between LAI and other variables important to define the SFY, such as SH and TILL Zhou and Shoko, 2011). Thus, assimilating only LAI and updating close related variables was not sustainable to inhibit the error inconsistency.…”
Section: Discussionmentioning
confidence: 99%